ETR : Enaileaf Henna / Ain Najiha Jasni - Jasni, Ain Najiha (2019)
Enaileaf henna is selling the henna products. I believe that girls out there love to wearing henna for some occassion. Enaileaf product comes with something that make easier to the customer for using it. For example, before this when we want to wearing henna, we need to prepare from first step which are pick the henna leaf, process and then only can apply the henna on your hands. But now, Enaileaf henna can directly apply to your hands and need to wait for a while and after that customers will get the beautiful colour of henna.